Unequal freedom: how race and gender shaped American citizenship and labor - Glenn, Evelyn Nakano (Harvard University Press, 2002)
The inequalities that persist in America have deep historical roots. Evelyn Nakano Glenn untangles this complex history in a unique comparative regional study from the end of Reconstruction to the eve of World War II. During this era the country experienced enormous social and economic changes with the abolition of slavery, rapid territorial expansion, and massive immigration, and struggled over the meaning of free labor and the essence of citizenship as people who previously had been excluded sought the promise of economic freedom and full political rights.After a lucid overview of the concepts of the free worker and the independent citizen at the national level, Glenn vividly details how race and gender issues framed the struggle over labor and citizenship rights at the local level between blacks and whites in the South, Mexicans and Anglos in the Southwest, and Asians and haoles (the white planter class) in Hawaii. She illuminates the complex interplay of local and national forces in American society and provides a dynamic view of how labor and citizenship were defined, enforced, and contested in a formative era for white-nonwhite relations in America.
Le chapitre « Citizenship: Universalism and Exclusion » a été donné en lecture au cours POL4212.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amériques; approches et analyses; cours; discipline; droits des femmes*; droits des personnes; histoire et politique; intersectionnalité; inégalités; pol4212; premier cycle; périodes historiques; racisme; racisme systémique; régions géographiques; sexisme; systèmes d'oppressions; thématiques; états-unis; études critiques de la race; études de genres

« Sex and the City » : la prostitution à l’ère des migrations mondiales - Robinson, Lillian S. (Recherches féministes, 2002)
Comme caractéristique du développement capitaliste, la migration économique a toujours entraîné le travail sexuel. À l’heure de la mondialisation, cela signifie pour beaucoup de femmes, qui émigrent du village à la grande ville dans leur propre pays ou du pays natal à l’étranger, un choix imposé par les circonstances. Cet article examine surtout la décision d’émigrer, les moyens empruntés et la situation à l’étranger de celles - la grande majorité, d’ailleurs – qui n’ont pas été victimes d’un trafic, mais qui ont exercé ce choix imposé. Le rôle dans l’émigration des travailleuses sexuelles et des clients « émigrés » en tant que touristes sexuels fait partie de la discussion, ainsi que d’autres caractéristiques économiques et culturelles.Summary As a feature of capitalist development, economic migration has historically entailed sex work as one of its components. In the age of globalization, this means a forced choice for many women, as they move from the village to the city in their own countries and across international borders. The present article focuses on the decision making process, the means of migration, and the experience in the urban site, national or international, of those – the vast majority – who have not been "trafficked", but have made this forced choice their life strategy. The impact on sex worker migration of customer "migration" in the form of sex tourism is discussed, along with the other economic and cultural factors.
Keywords: 1900-1999; afrique; amériques; approches et analyses; asie; capitalisme; cours; discipline; droits des femmes*; europe; féminisme du sud; féminisme décolonial; globalisation; his4860; histoire et politique; immigrantes clandestines; immigration; inde; industrie du sexe; inégalités; migration; pauvreté; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sexisme; sociologie; système colonial; systèmes d'oppressions; thématiques; tourisme sexuel; travail; travail des femmes*; travail du sexe